2003
DOI: 10.1590/s1413-70542003000100009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da semeadura a seco e tratamento de sementes na emergência, rendimento de grãos e outras características da soja [Glycine max (L.) Merrill]

Abstract: RESUMO O trabalho foi conduzido na Universidade Federal de Lavras-MG, em um Latossolo Roxo distrófi-co, no ano agrícola 94/95. Utilizou-se o delineamento blocos casualizados em esquema fatorial 2 x 4, compreendendo: semente tratada com fungicida Vitavax/Thiram P.M.e não tratada, e quatro períodos de seca (0, 7, 14 e 21 dias após a semeadura). A semeadura foi realizada em solo seco (6% de umidade), utilizando-se a cultivar Doko. As sementes apresentaram ótima performance até 14 dias, não sendo alterado o rendim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
5
0
3
Order By: Relevance
“…These results are consistent with those obtained by Rezende et al (2003) and Mertz et al (2009), where they observed positive effect of different treatments of soybean seeds with fungicides. The authors observed that the application of agrochemical fungicides led to higher values in the post-emergence development of soybean seedlings.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with those obtained by Rezende et al (2003) and Mertz et al (2009), where they observed positive effect of different treatments of soybean seeds with fungicides. The authors observed that the application of agrochemical fungicides led to higher values in the post-emergence development of soybean seedlings.…”
Section: Resultssupporting
confidence: 93%
“…Para estatura de plantas avaliada aos 28 dias, não houve diferença estatística entre os tratamentos (Tabela 1), o que concorda com resultados obtidos por REZENDE et al (2003), avaliando o tratamento de sementes de soja com fungicidas.…”
Section: Resultsunclassified
“…Resultados similares foram observados por HENNING et al (1991), os quais também constataram o efeito benéfico do tratamento de sementes de soja com fungicidas químicos para o controle de fungos existentes na semente e no solo. REZENDE et al (2003) observaram que, nos casos em que foi realizado o tratamento de sementes com fungicidas químicos, o estande inicial desejado não foi comprometido, mesmo com a semeadura coincidindo com períodos de estiagem, o que concorda com os dados obtidos no presente trabalho. Entretanto, na ausência de tratamento de sementes, ocorreu decréscimo na emergência de plântulas, com comprometimento do estande inicial.…”
Section: Resultsunclassified
“…Low quality seeds generally have the vigor and germination reduced; thereby yielding non-uniform crops, and crop fields with low plant population (Scheeren et al, 2010). According to Rezende et al (2003) the high productivity of a crop depends on the quality of the seeds used for the sowing, since the performance of these seeds is directly related to the historic of its production, of its processing, and of soil conditions on which such crop will be established.…”
Section: Introductionmentioning
confidence: 99%